Fixed income and interest rate derivative analysis - Britten-Jones, Mark 1963- (Butterworth-Heinemann, 1998)
Fixed Income and Interest Rate Derivative Analysis gives a clear and accessible approach to the analytical techniques of debt instrument valuation. Without using complicated mathematical abstractions, this text shows that the fundamentals of fixed income and interest rate derivate analysis can be easily understood when seen as a small number of simple economic concepts. * A comprehensive and accessible explanation of underlying theory, and its practical application * Case studies and worked examples from around the world's capital markets * How to use spreadsheet modelling in fixed income and interest rate derivative analysis Concepts inroduced in this book are reinforced and explained, not with the use of high-powered mathematics, but with actual examples of various market instruments and case studies from North America, Europe, Australia and Hong Kong. The text also contains review questions which aid the reader in their understanding. Mark Britten-Jones, BEcon, MA, PhD, is an Assistant Professor of Finance at the London Business School where he teaches Fixed Income Securities and Markets as part of a MBA and Master's course in Finance. A comprehensive and accessible explanation of underlying theory, and its practical application. Case studies and worked examples from around the world's capital markets. How to use spreadsheet modelling in fixed income and interest rate derivative valuation.
Includes bibliographical references and index. - Print version record
Keywords: Fixed-income securities; Derivative securities; Cash flow; Interest rate swaps; Valeurs mobilières à revenus fixes; Instruments dérivés (Finances); Marge brute d'autofinancement; Échanges de taux d'intérêt; BUSINESS & ECONOMICS; Investments & Securities; General